2019
DOI: 10.1007/s40473-019-00176-3
|View full text |Cite
|
Sign up to set email alerts
|

Remote Monitoring for Understanding Mechanisms and Prediction in Psychiatry

Abstract: Purpose of Review Technological advances offer the potential to better characterise the symptoms and mechanisms of psychiatric disorders. This review provides an overview of how remote monitoring might inform understanding of mood and anxiety disorders, and may be used by clinicians to predict clinical outcomes and treatment response. The review also discusses salient ethical issues and the field's future directions. Recent Findings A range of psychological and physiological remotely-collected data have been a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…data collected from individuals in their natural environment (10). This approach, sometimes referred to as 'digital phenotyping' (11), is defined as momentby-moment quantification of the individual-level human phenotype in-situ using data from personal digital devices (12). Previously, data collection and treatment monitoring has been limited to being carried out in person in clinical settings, thus providing data sets of limited size and utility.…”
Section: A Revolution In Data Collectionmentioning
confidence: 99%
“…data collected from individuals in their natural environment (10). This approach, sometimes referred to as 'digital phenotyping' (11), is defined as momentby-moment quantification of the individual-level human phenotype in-situ using data from personal digital devices (12). Previously, data collection and treatment monitoring has been limited to being carried out in person in clinical settings, thus providing data sets of limited size and utility.…”
Section: A Revolution In Data Collectionmentioning
confidence: 99%
“…The qualitative studies had identified that some found it too intrusive, whereas others worried they would become fixated on their own mental health, causing an anxiety of its own. 10 After seeing her last patient for the day, Dr Singh turned back to her computer. Flicking through the screens, she glanced through a collection of records the remote-monitoring outreach programme had flagged for her attention.…”
Section: Would She Know What Had Happened?mentioning
confidence: 99%
“…The qualitative studies had identified that some found it too intrusive, whereas others worried they would become fixated on their own mental health, causing an anxiety of its own. 10 Historical concerns around the medicalisation of everyday experience persisted in new forms. Part of her was relieved when Steve declined.…”
Section: A Vision Of the Futurementioning
confidence: 99%
“…Remote monitoring is concerned with the collection of clinically relevant data in ecologically-valid settings (9). Collecting time-stamped, longitudinal data in a patient's natural environment may provide a richer phenotype of mental distress than traditional forms of clinical assessment.…”
Section: Introductionmentioning
confidence: 99%
“…Digital phenotyping represents a form of remote monitoring where personal digital devices, such as smartphones or wearables, are used to collect clinically relevant data (10,11). This data may be used to identify new behavioral digital biomarkers, leading to the identification of novel phenotypes of psychiatric disorder and mental distress (9,12). Previous research, for instance, has identified geolocation and actigraphy variables associated with clinical features in BD (13,14).…”
Section: Introductionmentioning
confidence: 99%